2010
DOI: 10.1007/s00705-010-0627-y
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of norovirus GII.4 variants circulating in Korea in 2008

Abstract: Noroviruses are the enteric pathogens most commonly responsible for infectious gastroenteritis and outbreaks of foodborne illness. The GII.4 norovirus, in particular, is responsible for the majority of epidemics. Here, we present data on the distribution of norovirus genotypes in Chungnam, Korea, in 2008, measure genetic variation among GII.4 strains, and compare Korean GII.4 variants with reference strains based on the 237-bp junction of ORF1 and ORF2. We detected 139 different strains, which formed two disti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
15
1
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 34 publications
6
15
1
2
Order By: Relevance
“…In this study, the genotype GII.4 was the most prevalent, observed in 89.2% (58/65) of samples genotyped, present in almost every month over the two years. These results corroborate with those of other studies conducted in Brazil (Barreira et al 2010, Siqueira et al 2013) and in other countries (Park et al 2010, Vega et al 2011, Gómez-Santiago et al 2012), confirming the high circulation and impact of this genotype in cases of AGE.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the genotype GII.4 was the most prevalent, observed in 89.2% (58/65) of samples genotyped, present in almost every month over the two years. These results corroborate with those of other studies conducted in Brazil (Barreira et al 2010, Siqueira et al 2013) and in other countries (Park et al 2010, Vega et al 2011, Gómez-Santiago et al 2012), confirming the high circulation and impact of this genotype in cases of AGE.…”
Section: Discussionsupporting
confidence: 92%
“…There were many NoV genotypes circulating over the years, and GII.4 was the predominant genotype detected, which is in agreement with others [27,28]. In Brazil, GII.4 NoV is most frequently reported from emergency departments [5,6,29,30].…”
Section: Discussionsupporting
confidence: 84%
“…In this study, epidemic changes in NoV GII. in this study, which was one season earlier than previous reports [18][19][20]. Furthermore, GII.4-2009 and GII.4-2012 variants first emerged in South Korea a few months after the first global reports as shown [23,25].…”
Section: Discussioncontrasting
confidence: 45%
“…Several studies also revealed the emergence of NoV GII.4-2006b and GII.4-2007 variants [18][19][20]. However, the emergence of GII.4-2009 and recent GII.4-2012 variants have not been documented, and the epidemic changes of GII.4 variants have not been fully estimated on a long-term scale.…”
Section: Introductionmentioning
confidence: 93%